Gizeh, Ägypten: Die Reliefs aus dem Taltempel der Knickpyramide in Dahschur und andere Funde aus den Grabungen Ahmed Fakhrys - Alexanian, Nicole (e-Forschungsberichte des DAI, 2023)
Thanks to a grant of the Cultural Heritage Preservation Program of the German Ministry of Foreign Affairs the relief fragments and finds from the valley temple of the Bent Pyramid at Dahshur (about 2600 BC) in the magazines of Giza could be cleaned, restored, documented, catalogued and repacked in 2013. This work helps the Egyptian Antiquities Ministry to decide which objects shall be displayed in the „Grand Egyptian Museum“. The documentation of the relief fragments will result in a new attempt to reconstruct the decoration program of the valley temple, the oldest decorated pyramid temple of Egypt.